Management and outcomes of cardiac sarcoidosis: a 20‐year experience in two tertiary care centres. (31st October 2018) - Fussner, Lynn A.; Karlstedt, Erin; Hodge, David O.; Fine, Nowell M.; Kalra, Sanjay; Carmona, Eva M.; Utz, James P.; Isaac, Debra L.; Cooper, Leslie T.
Abstract : Aims: Cardiac sarcoidosis (CS) often presents with ventricular arrhythmias, heart block, and cardiomyopathy. The prognosis of CS with contemporary management is uncertain. We estimated the impact of baseline and treatment variables on left ventricular ejection fraction (LVEF), ventricular assist device placement, heart transplant, and death. Methods and results: We identified patients with CS seen from 1994–2014 at two large academic medical centres. All met the 2014 Heart Rhythm Society expert consensus criteria for diagnosis. From the 574 patients identified, 91 met inclusion criteria. Twenty‐two (24.2%) were diagnosed by endomyocardial biopsy. Cardiomyopathy was the primary presentation in 47 patients (51.6%). Within 90 days of diagnosis, 41 patients (45.0%) received prednisone alone, 29 (31.9%) received alternative immunosuppression with or without prednisone, and 21 (23.1%) received no immunosuppression. During follow‐up, 31 of 47 cardiomyopathy patients experienced improvement in LVEF, while 23 experienced decline in LVEF or clinical exacerbation, and 15 of 22 patients presenting with ventricular arrhythmia had recurrence. These results did not differ by treatment group. During a median follow‐up of 44 months for our cohort, 14 patients reached the composite endpoint of ventricular assist device placement, heart transplant, or death. Survival without the composite outcome did not differ by treatment group, but was worse among patients presenting with cardiomyopathy (log‐rank = 0.005). Conclusion: In a large series of CS subjects, rates of ventricular arrhythmia and heart failure events remain high with no treatment regimen clearly associated with better outcome. Patients with cardiomyopathy at diagnosis were more likely to reach the composite endpoint.